2013
DOI: 10.3923/jas.2013.286.293
|View full text |Cite
|
Sign up to set email alerts
|

Significant Factors Causing Cost Overruns in Large Construction Projects in Malaysia

Abstract: Once a construction projects fails in achieving effective cost performance, it will result to cost overmn. These ovemrns are caused from several factors which are very important to uncover for improving the cost performance. In Malaysia, not many research works have been carried out on study~ng cost performance factors. Hence, this study was conducted to identify the significant factors causing cost overrun in large construction projects in Malaysia. Questionnaire for the survey was developed based on 35 commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 14 publications
2
63
2
1
Order By: Relevance
“…It is a true fact that a contractor plays important role from initial to completion of the project, and therefore sufficient funds is required to ensure the smoothness of every single work activity. Financial and cash flow difficulties faced by contractor may lead to slow down and stop of the construction activities at site which results in the cost overrun [10].…”
Section: (I) Financial and Cash Flow Difficulties Faced By Contractormentioning
confidence: 99%
“…It is a true fact that a contractor plays important role from initial to completion of the project, and therefore sufficient funds is required to ensure the smoothness of every single work activity. Financial and cash flow difficulties faced by contractor may lead to slow down and stop of the construction activities at site which results in the cost overrun [10].…”
Section: (I) Financial and Cash Flow Difficulties Faced By Contractormentioning
confidence: 99%
“…In spite of the significance of the construction industry, it is faced with the problems of poor financial performance, high cost of project delivery, poor quality and material waste and failure to deliver value to clients on schedule [2,40]. Consequently, the industry has been extensively criticized for poor performance and ineffective productivity [42].…”
Section: Introductionmentioning
confidence: 99%
“…[26] reported that the indirect cost of rework is as high as six times the cost of rectifying failures. Studies have revealed that the consequence of poor quality work such as rework are; denying clients value for their monies; dissatisfied customers; unsafe structures; contract disputes; battered reputation; resource wastage; loss of business; loss of profit/revenue; reduce market share; and increase time and cost of construction; extra charges, and increased professional fees [2,6,11,15,27,31,34,35,38,42,44,47]. [33] assessed rework cost of selected building projects in Ondo state, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[9] opined that ineffective material planning and control on construction sites could result to poor performance and unplanned outcomes of construction projects. Construction projects are faced with severe problems of time and cost overruns, as well as construction waste ( [10], [11], [12]). According to [13] any material apart from earth material which needs to be transported elsewhere to the construction sites or used within the construction site itself for the purpose of land filling, incineration, recycling, reusing, or composting rather than the intended specific purpose of the project due to material change excess nonuse, or noncompliance with the specifications or being a byproduct of the construction process is regarded as construction waste.…”
Section: Introductionmentioning
confidence: 99%